2022
DOI: 10.1021/acs.energyfuels.2c01506
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Catalytic Activation Promoting Pore Development of Zhundong Coal-Based Activated Coke: A Compared Study with Conventional Carbonization–Activation Combined Process

Abstract: Hierarchically porous activated coke is widely applied in pollutant removal due to its excellent molecule adsorption and transportation ability. Catalytic activation with the participation of alkali/alkaline earth metal salt has been reported to be effective for constructing hierarchical pore configuration; however, the technical condition remains to be explored for providing guidance to practical preparation process. Herein, the relationship between the porous structure of Zhundong coal-based activated coke a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
2
Order By: Relevance
“…At 675 °C, the specific surface area slightly decreased, but it rapidly increased at 800 °C, which is basically consistent with the trend in the iodine value. However, the results are inconsistent with the conclusion of Chen et al, which may be caused by the different raw materials. Chen et al selected raw materials with a high volatile content (33.52%) and strong reactivity that can undergo intense reactions at lower carbonization temperatures.…”
Section: Preparation Of Caccontrasting
confidence: 89%
See 2 more Smart Citations
“…At 675 °C, the specific surface area slightly decreased, but it rapidly increased at 800 °C, which is basically consistent with the trend in the iodine value. However, the results are inconsistent with the conclusion of Chen et al, which may be caused by the different raw materials. Chen et al selected raw materials with a high volatile content (33.52%) and strong reactivity that can undergo intense reactions at lower carbonization temperatures.…”
Section: Preparation Of Caccontrasting
confidence: 89%
“…However, the results are inconsistent with the conclusion of Chen et al, which may be caused by the different raw materials. Chen et al selected raw materials with a high volatile content (33.52%) and strong reactivity that can undergo intense reactions at lower carbonization temperatures. As the heating rate increased (7, 10, and 13 °C/min), the specific surface area and iodine value showed a trend of first increasing and then decreasing, and the maximum specific surface area and iodine value were obtained at 10 °C/min.…”
Section: Preparation Of Caccontrasting
confidence: 89%
See 1 more Smart Citation
“…From the HETEM images, it is found that the graphite layers are discontinuous for all HPCs, leading to the formation of many three‐dimensional porous structures. It should be related to the template function of MgO, while the decrease of carbon walls comes from the etching of KCl [14] . From these observations, it is confirmed that the combination of KCl and MgO can effectively promote the formation of porous and thin wall carbon structures.…”
Section: Resultsmentioning
confidence: 68%
“…It should be related to the template function of MgO, while the decrease of carbon walls comes from the etching of KCl. [14] From these observations, it is confirmed that the combination of KCl and MgO can effectively promote the formation of porous and thin wall carbon structures. Apparently, the three-dimensional porous structures with thinner wall structures are very beneficial to achieve high electrochemical performance.…”
Section: Resultsmentioning
confidence: 69%